PENGENTASAN ANGKA KEMISKINAN DI INDONESIA TAHUN 2015-2019 - Anggraeni, Rachvianti (Transpublika Publisher, 2022)
Poverty that occurs in Indonesia is caused by many interrelated factors, education, and health are problems that are often related to poverty. The purpose of this study was to analyze the effect of education, unemployment, and health on poverty. This research is descriptive quantitative research. The data used in this study is secondary data obtained from the Central Statistics Agency (BPS) Indonesia. The period in this study is five years, namely 2015 - 2019. The data analysis technique used is multiple linear regression analysis technique. The results showed that the random effect model was the best model. Education and Unemployment show significant results and are positively related to poverty. Meanwhile, health shows insignificant results and is negatively related to poverty in Indonesia.